A Retrospective Study of Lung Transplantation in Patients With Lymphangioleiomyomatosis: Challenges and Outcomes - Zhang, Ji; Liu, Dong; Yue, Bingqing; Ban, Le; Zhou, Min; Wang, Hongmei; Lv, Jian; Wu, Bo; Zhai, Zhenguo; Xu, Kai-Feng; Chen, Wenhui; Chen, Jingyu (Frontiers in Medicine, 2021)
Background: Lymphangioleiomyomatosis (LAM) is a rare systemic disease that generally leads to progressive decline in pulmonary function. Experience, especially from Asian population, including combined drug therapy before and after lung transplantation (LT) in LAM, is still limited. This study aimed to summarize the clinical data from patients with pulmonary LAM who underwent LT at centers in China. Methods: A retrospective review of all patients with LAM undergoing LT at two largest centers in China between 2010 and 2018 was conducted. Pre- and post-transplant data were assessed and analyzed. Results: Overall, 25 patients with LAM underwent bilateral LT. The mean age was 35.0 ± 8.6 years at diagnosis and 36.8 ± 9.3 years at the time of transplant. Before LT, only six patients could complete pulmonary function test; the reachable mean forced expiratory volume in one second (FEV1) before LT was 15.9% ± 6.9%. Twenty-one patients (84%) had recurrent pneumothorax, four (16.0%) of which required pleurodesis. Eight patients (32%) were treated with sirolimus pre-transplant for 3.9 years (1–9 years). The average intra-surgery bleeding volume was 1280 ± 730 mL in need of a transfusion of 1316 ± 874 mL due to moderate-to-severe adhesion and pre-transplant pleurodesis. The causes of death of four patients (16%) included primary graft dysfunction, bronchial dehiscence with long-term use of sirolimus, and uncontrollable infections. The median follow-up time from LT was 41.1 ± 25.0 months. Conclusions: LT for LAM patients from Asian population has been reinforced from data that we presented. Peri-transplantation use of sirolimus and LAM-related complications should be further defined and under constant surveillance.